2014
DOI: 10.1245/s10434-014-4070-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Malignant Neoplasms after Osteosarcoma: Early Onset and Cumulative Alkylating Agent Dose Dependency

Abstract: High cumulative AAS is an independent risk factor for SMN and its early-onset development after osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The Childhood Cancer Survivor Study (CCSS) and other cohorts of childhood cancer survivors have reported extensively on the incidence of and risk factors for subsequent neoplasms . Therapeutic radiation has been strongly associated with development of subsequent neoplasms; however, dose-response relationships have also been identified for specific chemotherapeutic agents, including alkylating agents and epipodophyllotoxins . With this knowledge, childhood cancer treatment has been modified over time with the hope of reducing subsequent neoplasm risk, while maintaining or improving 5-year survival …”
Section: Introductionmentioning
confidence: 99%
“…The Childhood Cancer Survivor Study (CCSS) and other cohorts of childhood cancer survivors have reported extensively on the incidence of and risk factors for subsequent neoplasms . Therapeutic radiation has been strongly associated with development of subsequent neoplasms; however, dose-response relationships have also been identified for specific chemotherapeutic agents, including alkylating agents and epipodophyllotoxins . With this knowledge, childhood cancer treatment has been modified over time with the hope of reducing subsequent neoplasm risk, while maintaining or improving 5-year survival …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a long follow-up period is needed after primary treatment for OS to detect both SPMs as well as recurrence, metastasis, or multiple OS ( 9 , 24 , 35 , 36 ). SPMs after OS can be fatal ( 6 , 7 ), and together with metastasis, chemotherapy response, tumor characteristics, patient characteristics, surgical margins, and toxicity, SPMs are an important prognostic factor ( 37 ). Indeed, the prognosis is poor once SPMs occur ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study by Kim et al, a high cumulative alkylating agent dose was found to be an independent risk factor for second malignant neoplasms and its early development after osteosarcoma treatment [ 10 ]. In our patient, the cumulative dose of ifosfamide used was 21.6 gm/m2.…”
Section: Discussionmentioning
confidence: 99%